Strašnoe snovidenie Ivana Fedoroviča Špon'ki. Onejričeskaja poetika rannego Gogolja - Benčić, Živa (Array, 2011)
The article focuses on some aspects of oneiric poetics in early Gogol, primarily in his short story “Ivan Fiodorovich Shponka and His Aunt” from the second part of the collection Village Evenings Near Dikanka. Analyzing the hero’s dream with which the story ends, with respect to its emotional colouration, thematic constitution and function in the narrative structure, the author of this article comes to the following conclusions: The dream of Ivan Fiodorovich Shponka which reflects the hero’s panic fear of women, when compared to some dreams from earlier short stories, no longer plays any significant role in the resolution of the narrative collisions of the syuzhet ; however, its role in the protagonist’s psychological characterization increases. The question whether the sense of fear that Gogol projected to his literary character stems from his personal subconscious or from the collective memory is not relevant for the credibility of Shponka’s dream. His nightmare and the way it is described in the analyzed short story has shown itself to be of extreme significance for the further development of Gogol’s prose. More precisely, the oneiric category allows Gogol not only to explore an interesting deviation from the experiential reality, but also to open up to several reality dimensions that would, otherwise, beyond the frame of a dream, remain inconspicuous for a long while in literature. Thanks to Shponka’s oneiric world picture – alogical and absurd, Gogol distances himself from the romantic, as well as from the realistic sense of the real, announcing the poetics of the absurd and surrealism that will come a whole century later.